Interpretation of Verses About Nusyuz, Syiqaq and Their Solution: Normative Psychological and Theological Approaches (An-Nisa 34-35 And 128) - Kurniawan, Dede; Sayehu, Coauthor (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
The aim of this research is to analyze the interpretation of verses about nusyuz, syiqaq and their solutions: normative psychological and theological approaches (an-nisa 34-35 and 128). The method used in this research is qualitative with a descriptive approach, data sources are obtained from books, dissertations, articles. Data collection techniques via the internet, while the data analysis technique is literature study. The conclusions in this research are (1). Nusyuz and its Completion (An-Nisa 34): a. Psychological Approach: These actions, especially advice, serve to relieve the tension of husband and wife conflicts. b. Normative Theological Approach: Handling nusyuz in Islam must be done wisely and while maintaining justice and compassion. (2). Syiqaq and its Resolution (An-Nisa 35): a. Psychological Approach: Mediation provides an opportunity for couples to calm themselves and see the conflict from a different perspective through the help of a third party in accordance with Islamic law. b. Normative Theological Approach: The appointment of a hakam is the final step in efforts to maintain domestic harmony, showing the importance of peaceful resolution before making decisions such as divorce. (3). Shiqaq and Peace Agreements (An-Nisa 128): a. Normative Theological Approach: Peace is an important value in Islamic law. b. Psychological Approach: Peace agreements allow for compromises that can help maintain harmony. Keywords : Nusyuz, Syiqaq, Psychological Approach, Normative Theological Approach, QS An-Nisa: 34-35 and 12.